Synthesis, Characterization, Thermal Study, Biological Activity and Corrosion Inhibition of New Ligand Derived from Butanedioyl Dichloride and Some Selective Transition Metal Complexes - Enass J. Waheed (Journal of Global Pharma Technology, 2019)
The new ligand [N1,N4-bis((1H-benzo[d]Glyoxalin-2-yl)carbamothioyl)Butanedi amide] (NCB) derived from Butanedioyl diisothiocyanate with 2-aminobenz imidazole was used to prepare a chain of new metal complexes of Cr(III), Mn(II), Co(II), Ni(II), Cu(II), Pd(II), Ag(I), Cd(II) by general formula [M(NCB)]Xn ,Where  M= Cr(III), n=3, X=Cl; Mn(II), Co(II), Ni(II), Cu(II), Pd(II), Cd(II) ,n=2 , X=Cl; Ag(I), n=1, X=NO3. Characterized compounds on the basis of 1H, 13CNMR (for (NCB), FT-IR and U.V spectrum, melting point, molar conduct, %C, %H, %N and %S, the percentage of the metal in complexes %M, Magnetic susceptibility, thermal studies (TGA),while its corrosion inhibition for mild steel in Ca(OH)2 solution is studied by weight loss. These measurements indicate that (NCB) coordinates with the metal ion in a hexadentate manner through the sulfur and nitrogen atoms and the octahedral structure of these complexes is suggested. The anti-bacterial activity of the complexes against two types of bacterial Staphylococcus Aureus (+) and Escherichia Coli (_) for the metal complexes was higher than for free ligand (NCB).Keywords: Butanedioyl dichloride, Corrosion inhibition, Biological activity.